Hematopoeitic Stem Cell Donation in Children: A Review of the Sibling Donor Experience - Wiener, Lori S. (2007)
Hematopoietic Stem Cell Transplant (HSCT) represents the second most frequent major organ transplant in the United States. Compared to other family members, siblings are more likely to be immunologically matched with the recipient and therefore are often the most suitable donors. Due to a dearth of information on the positive and adverse effects of HSCT on pediatric sibling donors, we sought to examine available data. Eight published reports assessing the pediatric sibling donor experience were identified in the literature. Studies were predominately small (n < 44) and cross-sectional. Results suggest a range of psychological distress responses with higher distress in pediatric donor than non-donor siblings. Recommendations include future longitudinal research on sibling donor psychosocial adjustment, identification of sibling donors at high risk for maladaptive responses, and development of educational and psychosocial interventions for this overlooked pediatric population.